O prêmio salarial e a penalidade por sobre-educaç\~ao de doutores: Estimativas para o setor privado brasileiro - Daniel Gama e Colombo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This paper aims to estimate the association between, on the one hand, the hourly wages of private sector employees in Brazil, and, on the other, a doctorate degree and overeducation of workers with a Ph.D. The study is based on microdata from the Annual Social Information Report (Rais) for the 2010-2021 period. The share of overeducation among employees with a Ph.D. degree in the educational and non-educational sectors are 45.9% and 84.2%, respectively. The results indicate a low doctorate wage premium of approximately 1.1% in the educational sector and 8.7% in non-educational sectors. No evidence was found of a wage penalty for overeducation of Ph.D.s in the educational sector, while in non-educational sectors the associated wage reduction is of approximately 6.4%. The conclusions highlight the importance of policies to increase the demand for Ph.D. workers and the better use of these professionals in activities that match their educational attainment.
Keywords: I23; I26; J31; 330; doctorate; wage premium; overeducation; human capital; graduate education